Spirit Moral Pekerja Bangunan (Studi Kasus Fenomenologi Buruh Pekerja Bangunan di PT. Griya Karya Sentosa) - Gigih Wahyu Pratomo (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2020)
Research on construction workers is a phenomenological study using a qualitative method approach. This study aims to reveal the inter-subjective meaning behind the interpretation of a manual construction labor. It shows that individuals experience institutional awareness of the objects that appear in front of them, consciousness is a reality that belongs entirely to the subject. The awareness that is internal to the object will become an active decision, which in the end displays an inspiration to the life play he is living in, even ignoring other judgments about the visible object. Through phenomenological studies, in-depth research gets a complete picture of how the subject perceives the existence of his life and displays decisions from his life picture. Although from time to time he realizes that he is a "wong cilik", he finally survives today's reality and prefers the principle of "dahulukan selamat" which is a spirit of morality and compromise to continue to survive